2013
DOI: 10.1089/cell.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Are an Attractive Donor Cell Type for Production of Cloned Pigs As Well As Genetically Modified Cloned Pigs by Somatic Cell Nuclear Transfer

Abstract: The somatic cell nuclear transfer (SCNT) technique has been widely applied to clone pigs or to produce genetically modified pigs. Currently, this technique relies mainly on using terminally differentiated fibroblasts as donor cells. To improve cloning efficiency, only partially differentiated multipotent mesenchymal stem cells (MSCs), thought to be more easily reprogrammed to a pluripotent state, have been used as nuclear donors in pig SCNT. Although in vitro-cultured embryos cloned from porcine MSCs (MSCs-emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
(52 reference statements)
3
38
0
Order By: Relevance
“…The higher appropriate remodeling of stem cell-NT derived embryos has proved in different species (Bosch et al, 2006, Faast et al, 2006, Kumar et al, 2012, Lee et al, 2006, Rideout et al, 2000. Some reports, however, have rejected transcendence of stem cells over somatic cells in normal reprogramming of NT derived embryos (Berg et al, 2007, Li et al, 2013, Sung et al, 2006. In the first report on the use of bovine MSCs for NT, no priority in developmental potential was observed in stem cell derived embryos compared to non-stem cell derived counterparts (Kato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The higher appropriate remodeling of stem cell-NT derived embryos has proved in different species (Bosch et al, 2006, Faast et al, 2006, Kumar et al, 2012, Lee et al, 2006, Rideout et al, 2000. Some reports, however, have rejected transcendence of stem cells over somatic cells in normal reprogramming of NT derived embryos (Berg et al, 2007, Li et al, 2013, Sung et al, 2006. In the first report on the use of bovine MSCs for NT, no priority in developmental potential was observed in stem cell derived embryos compared to non-stem cell derived counterparts (Kato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group and others have described the generation of TG animals expressing microorganism-derived digestive enzymes such as phytase and cellulase specifically in the salivary glands for improvements of feed nutrient utilization11212223. Here we report the production of a therapeutic protein, the human nerve growth factor (hNGF), in the salivary glands of TG mice.…”
mentioning
confidence: 92%
“…Instead these workers suggested that the development of cloned embryos should be assessed in terms of the number of blastocyst that develop to term rather than the number of embryos that develop to the blastocyst stage. Interestingly Lee et al [8] and Li et al [9] have reported that porcine MSCs increase blastocyst development and cell number as well as live born when these cells are used for SCNT compared with fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that the use of porcine mesenchymal stem cells (MSCs) isolated from the bone marrow can increase the proportion of SCNT embryos that develop to the blastocyst stage compared with adult fibroblasts obtained from the same animal (Faast et al). Subsequent studies by Lee et al [8] and Li et al [9] have suggested that blastocyst cell number and development to term is also increased when MSCs are used compared with fibroblasts. MSCs are found in the stromal compartment of the bone marrow and can be differentiated into adipocytes, chondrocytes and osteocytes [10].…”
Section: Introductionmentioning
confidence: 99%